View from the steps on the first level of the adhisthana - Temples of India Project Team (Jio Institute, 2024)
View from the steps on the first level of the adhisthana. The adhisthana has a chandrashila (moonstone) on the landing (seen in the foreground) of the first set of steps and the beginning (seen in the centre) of the second set of steps. The moonstone is a hemispherical stone in the shape of the moon which is often placed at the entrance of Hindu temples and is designed to resemble a lotus flower.